“An infusion of the modern spirit into the ancient form”: Textual Objects and Historical Consciousness in George Eliot’s Romola - Burkert, Mattie (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
In George Eliot’s Romola, manuscripts represent the ability of objects to embody the past. Through various characters’ interactions with manuscripts, Eliot explores competing ways of using and valuing history, from Bardo’s obsessive collecting to Savonarola’s ideological co-optation. As the story progresses, however, manuscripts all but disappear and are replaced by printed texts. Through this depiction of technological change, Eliot advances her case for a particular kind of historical consciousness, one that engages critically—rather than fetishistically or opportunistically—with the past. Print, Eliot suggests, allows history to become widely accessible for public consumption, thereby weakening the aura of the past and allowing readers to simultaneously recognize its alterity and its intimate relationship to the present. Eliot suggests that the role of history is to guide and advance the interests of humanity in the present; as such, she uses Renaissance anxieties over the movement from manuscript to print to interrogate Victorian concerns surrounding the proliferation of inexpensive printed materials.